Examining Illocutionary Acts: Male and Female Judges’ Comments on Indonesia’s Next Top Model - Zalikha; Dian Budiarti (SPHOTA: Jurnal Linguistik dan Sastra, 2024)
This article delves into the linguistic and discursive aspects of communication, exploring the application of theories proposed by J.L. Austin (1975) and John Searle (1969) to understand the illocutionary acts employed by the male and female judges in Indonesia's Next Top Model. Within the context of reality television, where judgments and critiques are integral components, the language used by judges holds particular significance. This study aims to delve into the illocutionary acts employed by male and female judges in the popular television show "Indonesia's Next Top Model Cycle 3." The research method for this study employed a qualitative research approach, involved describing data from real-life situations or phenomena in their natural context within the reality show to explore the nuances and meanings of illocutionary acts in judges' comments. A sample of episodes from Indonesia's Next Top Model Cycle 3 was selected for analysis, ensuring representation of both male and female judges' comments. The dataset consisted of 266 utterances, 132 utterances from male judges' comments and 134 utterances from female judges' comments. In this study, it is found that the female judges had a greater variety of speech acts where they used all types of speech acts when giving comments. Whereas male judges only used three types of speech acts. The most dominant type of speech act of both male and female judges is assertives/representatives. It is inferred that both male and female judges are having or showing a confident and forceful personality in their utterances. In this study, it can also be seen that female judges are more to the point or overt than male judges.